Paper‐Based Electrical Respiration Sensor. Issue 19 (5th April 2016) - Güder, Firat; Ainla, Alar; Redston, Julia; Mosadegh, Bobak; Glavan, Ana; Martin, T. J.; Whitesides, George M.
Abstract: Current methods of monitoring breathing require cumbersome, inconvenient, and often expensive devices; this requirement sets practical limitations on the frequency and duration of measurements. This article describes a paper‐based moisture sensor that uses the hygroscopic character of paper (i.e. the ability of paper to adsorb water reversibly from the surrounding environment) to measure patterns and rate of respiration by converting the changes in humidity caused by cycles of inhalation and exhalation to electrical signals. The changing level of humidity that occurs in a cycle causes a corresponding change in the ionic conductivity of the sensor, which can be measured electrically. By combining the paper sensor with conventional electronics, data concerning respiration can be transmitted to a nearby smartphone or tablet computer for post‐processing, and subsequently to a cloud server. This means of sensing provides a new, practical method of recording and analyzing patterns of breathing. Abstract : Internet‐enabled paper‐based sensor : A simple paper‐based sensor relying on changes in the humidity caused by breathing was fabricated (see picture). The electrical conductivity of the cellulose adsorbent varied as it was loaded with water from humid exhaled air.